PHYTOCHEMICAL SCREENING AND GAS CHROMATOGRAPHY-MASS SPECTROSCOPY ANALYSIS OF METHANOLIC EXTRACT OF Mucuna bracteata SEEDS - ABIGAIL J. M.; DASHAK D. A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Plant and plant-based medicaments are the basis of many modern pharmaceuticals which are use for diverse ailments. Mucuna bracteata is a velvet beans plant, a tropical legume mostly found in Africa, tropical Asia and India which are widely naturalized and cultivated. It is a climbing shrub with long vines, its seed pod are covered in loose hairs. The plant is known for its medicinal properties. The aims of the study were to screen for phytochemicals and characterized the bioactive chemicals constituents of methanolic extract of Mucuna bracteata seedplant using Gas Chromatography-Mass Spectroscopy and Infared spectroscopy. The dried seeds of the plant were pulverized and extracted with methanol by using soxhlet extractor for 12 hours at constant temperature of 60oC. The crude extracts were then concentrated using rotary evaporator. Column chromatography and thin layer chromatography were carried out on the crude extract and the fractions respectively. The preliminary phytochemical screening was performed on the crude extract and the result revealed the presence of alkaloids, glycosides, terpenoids, steroids, flavonoids, tannins, anthraquinones and saponins. GC-MS and IR spectra data of the methanol fraction reveal the presence of many organic compounds which are mostly fatty acid, esters, alcohols, amino acid, alkanes, and amines. The compounds identified are: hexadecanoic acid, hexadecanoic acid methyl ester, 9-octadecanoic acid (oleic acid), tetradecanoic acid ethyl ester (myristic acid), hexadecanoic acid ethyl ester, dodecanoic acid ethyl ester, dodecane, octadecanoic acid (stearic acid), 9, 12, 15-octadecanoic acid, 9-octadecanoic acid methyl ester (recenolic acid methyl ester)